Home experiences and homemaking practices of single Syrian refugees in an innovative housing project in Amsterdam. (September 2020) - Kim, Kyohee; Smets, Peer
Recent socio-political situations in the Middle East and elsewhere have resulted in a large number of refugees searching for new places to settle. To understand how a new place could become a home, the authors conducted qualitative research in the Netherlands. The study looked at the home experiences and (micro)homemaking practices of young Syrian refugees in an innovative housing project in Amsterdam. In this project, Dutch and Syrian young adults are housed together to foster integration. This article also looks at Boccagni's model for understanding immigrant live-in workers' homes. The authors further develop the model by introducing a mobility lens, which offers the possibility of elaborating on theoretical notions between now-and-then and here-and-there and the empirical findings derived from this study.